Prognostic Significance of Clusterin Expression in Advanced-Stage Cervical Cancer Treated With Curative Intended Radiotherapy. Issue 3 (1st March 2012) - Watari, Hidemichi; Kinoshita, Rumiko; Han, Yimin; Wang, Lei; Hosaka, Masayoshi; Taguchi, Hiroshi; Tsuchiya, Kazuhiko; Tanaka, Shinya; Shirato, Hiroki; Sakuragi, Noriaki
Abstract : Objective: Overexpression of clusterin (CLU), an antiapoptotic molecule, has been reported to induce resistance to radiotherapy (RT) in a variety of cancer cell types. The aim of this study was to evaluate the significance of CLU expression to predict survival of patients with advanced-stage cervical cancer who received curative intended RT. Methods: Biopsy tissue specimens of advanced-stage cervical cancer before curative intended RT were obtained from 34 patients who were treated at Hokkaido University Hospital between 1998 and 2008 and whose complete medical records were available. The expression of CLU protein was analyzed by immunohistochemistry. Findings were evaluated in relation to several clinicopathological factors. Survival analyses were performed using the Kaplan-Meier curves and the log-rank test. Independent prognostic factors were determined by multivariate Cox regression analysis. Results: Clusterin protein was mainly present in the cytoplasm of cervical cancer cells. The expression of CLU protein in cervical cancer tissues before curative intended RT was not significantly related to any clinicopathological factors analyzed, including age, clinical stage, histologic type, and response to RT. Univariate analysis on prognostic factors showed that histologic type ( P = 0.001), and CLU expression ( P = 0.02) were related to survival. Multivariate analysis revealed that both histologic type ( P = 0.002), and CLU expression ( P = 0.02) were independent prognostic factors for overall survival. Conclusion: We conclude that CLU could be a new molecular marker to predict overall survival of patients with advanced-stage cervical cancer treated with curative intended RT.